Erratum: Complete genome sequence of Streptococcus agalactiae serotype III, multilocus sequence type 283 strain SG-M1 [Genome Announc, 3, 5 (2015) (e01188-15)], DOI: 10.1128/genomeA.01188-15 - Mehershahi, K.S (2020)
10.1128/genomeA.01585-15